1977
DOI: 10.2307/350906
|View full text |Cite
|
Sign up to set email alerts
|

Fertility during Marital Disruption

Abstract: The frequent occurrence of childbirth during periods of marital disruption is discussed. Life table procedures based on 1970 information show, from a sample of 1,054 women, that slightly more than 25% of separated, divorced, or widowed women had given birth within 48 months of marital disruption. The variables affecting these statistics are described in terms of race, educati9n, parity, and, most importantly, age at time of disruption. A multivariate analysis is used to explore the cumglative prevalance of hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…One interpretation is that some women, who wish to avoid a marital break-up, got pregnant near the year in which the law was enacted (or close to the date of marital disruption) and other women got pregnant immediately after divorce (in hopes of reconciliation) and, thus, gave birth sometime during the first postlaw year. In Downloaded by [University of Nebraska, Lincoln] at 20:00 13 October 2014 Social Biology support of this interpretation, Rindfuss and Bumpass (1977) found that births during marital disruption seem to cluster either near the date of dissolution or within a year following separation and divorce. Another interpretation of childbearing during marital disruption might be that these births, occurring near the date of dissolution or within a year following separation and divorce, are fathered by someone other than the former spouse, and perhaps are a factor in the marital dissolution (Rindfuss and Bumpass, 1977).…”
Section: Discussionsupporting
confidence: 49%
“…One interpretation is that some women, who wish to avoid a marital break-up, got pregnant near the year in which the law was enacted (or close to the date of marital disruption) and other women got pregnant immediately after divorce (in hopes of reconciliation) and, thus, gave birth sometime during the first postlaw year. In Downloaded by [University of Nebraska, Lincoln] at 20:00 13 October 2014 Social Biology support of this interpretation, Rindfuss and Bumpass (1977) found that births during marital disruption seem to cluster either near the date of dissolution or within a year following separation and divorce. Another interpretation of childbearing during marital disruption might be that these births, occurring near the date of dissolution or within a year following separation and divorce, are fathered by someone other than the former spouse, and perhaps are a factor in the marital dissolution (Rindfuss and Bumpass, 1977).…”
Section: Discussionsupporting
confidence: 49%
“…The analysis was limited to the effects of postmarital fertility. Postdissolution fertility was excluded from the analyses, a nuisance factor (Chester, 1972;Monahan, 1955;Rindfuss & Bumpass, 1977) that was not excluded in some previous studies (e.g., Jacobson, 1950). Thornton used data only on marriages that were terminated by discord.…”
Section: Empirical Support For the Deduction And Possible Alternative...mentioning
confidence: 99%
“…Analyses with data only on women's children show mixed effects. On the one hand, some studies have found a clearly negative association between the risk of childbearing and the previous parity (Rindfuss and Bumpass 1977;Clarke et al 1993;Lillard, Panis, and Upchurch 1994); on the other hand, other analyses have found a non-linear negative effect of such a parity (Wineberg 1990;Jefferies, Berrington, and Diamond 2000), while still others have demonstrated no effect (Griffith, Koo, and Suchindran 1985;Diamond, Clarke, and Clarke 1995). These latter results suggest that the effect of stepchildren may not be as strong as we could expect, and that the first shared child of a second union may have a unique value which interacts with the value of those children born during the first marriage.…”
Section: Predictors Of Childbearing After a Marital Dissolution: Repamentioning
confidence: 99%